Comparative Potential of Zinc Sulfate, L-Carnitine, Lycopene, and Coenzyme Q10 on Cadmium-Induced Male Infertility. (30th June 2022) - Iftikhar, Ayesha; Akhtar, Muhammad Furqan; Saleem, Ammara; Riaz, Amjad; Zehravi, Mehrukh; Rahman, Md. Habibur; Md Ashraf, Ghulam
Abstract : The human exposure to toxic chemicals and heavy metals is one of the main predisposing factors contributing to male infertility. Acute exposure to cadmium chloride results in testicular damage and infertility. The purpose of the present study was to investigate and compare the curative effect of coenzyme Q10 (CoQ10), lycopene, L-carnitine (LC), and zinc sulfate against the cadmium-induced infertility in male Wistar rats. Cadmium chloride (0.4 mg/kg/day) was orally administered to rats for three consecutive days. Then, oral administration of different treatments (i.e., LC 100 mg/kg, CoQ10 20 mg/kg, lycopene 4 mg/kg, zinc sulfate 6 mg/kg, and a combination LC-CoQ10 at 500/50 mg/kg) was carried out for 30 days. The impact of different treatments on semen parameters, such as sperm count and motility, testicular antioxidants, and serum testosterone, was determined. Furthermore, the morphology of epididymis sperms and histopathology of rat testes were also assessed. Cadmium exposure decreased the sperm count, progressive sperm motility, testosterone, superoxide dismutase (SOD), and catalase and reduced glutathione (GSH). It also caused banana sperm tail, bent sperm head, vacuolization of seminiferous tubules, and oligospermia in rat testes. All treatments with nutraceuticals improved sperm count, sperm morphology, serum testosterone, vacuolization of seminiferous tubules, and oligospermia in diseased rats. Treatment with lycopene, LC, and LC-CoQ10 improved progressive sperm motility and other parameters and increased SOD, GSH, and CAT in the rat testes. CoQ10 also increased SOD activity in rat testes' tissue homogenates. It is concluded from the current study that all nutraceuticals partially improved reproductive toxicity of cadmium. The administration of lycopene and a high-dose combination of LC-CoQ10 were more efficacious in treating cadmium-induced infertility than other treatments. Treatment of cadmium-exposed rats with lycopene, LC, CoQ10, and LC-CoQ10 improved sperm count and motility through reduction of testicular oxidative stress and improving serum testosterone.